Decision Making as a Learned Skill in Mice and Humans - Posner, Michael I.; Weible, Aldis P.; Voelker, Pascale; Rothbart, Mary K.; Niell, Cristopher M. (Frontiers in Neuroscience, 2022)
Attention is a necessary component in many forms of human and animal learning. Numerous studies have described how attention and memory interact when confronted with a choice point during skill learning. In both animal and human studies, pathways have been found that connect the executive and orienting networks of attention to the hippocampus. The anterior cingulate cortex, part of the executive attention network, is linked to the hippocampus via the nucleus reuniens of the thalamus. The parietal cortex, part of the orienting attention network, accesses the hippocampus via the entorhinal cortex. These studies have led to specific predictions concerning the functional role of each pathway in connecting the cortex to the hippocampus. Here, we review some of the predictions arising from these studies. We then discuss potential methods for manipulating the two pathways and assessing the directionality of their functional connection using viral expression techniques in mice. New studies may allow testing of a behavioral model specifying how the two pathways work together during skill learning.